2012
DOI: 10.1007/s00535-012-0631-y
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: mortality and serious adverse events of peginterferon plus ribavirin therapy for chronic hepatitis C

Abstract: The mortality rate during PEG-IFN/RBV therapy was acceptably low, but the rate of SAEs was not negligible in a treatment for a benign disease, and the rate was affected by treatment regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 93 publications
1
15
1
Order By: Relevance
“…The difference between the two groups in time to withdrawal from treatment due to adverse events was analyzed using the multivariate Cox proportional hazards regression model. 18) In the analysis, the following variables were considered to be confounding, based on the medical implications of previous reports 11,15,16,19) : age, sex, platelet count, ALT level, HCV viral load, and treatment experience. The analysis taking into consideration regional variation was performed using the Cox proportional hazards regression with a shared frailty model (frailty model).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between the two groups in time to withdrawal from treatment due to adverse events was analyzed using the multivariate Cox proportional hazards regression model. 18) In the analysis, the following variables were considered to be confounding, based on the medical implications of previous reports 11,15,16,19) : age, sex, platelet count, ALT level, HCV viral load, and treatment experience. The analysis taking into consideration regional variation was performed using the Cox proportional hazards regression with a shared frailty model (frailty model).…”
Section: Methodsmentioning
confidence: 99%
“…6,7) Severe adverse events are especially common with HCV genotype 1 infection, because the sustained virologic response rate is relatively low. [9][10][11] Studies investigating differences in adverse events between PEG-IFN α-2a combined with ribavirin and PEG-IFN α-2b combined with ribavirin, including the safety outcomes of randomized clinical trials in Japan and other countries, as well as the pooled analysis of these studies, have suggested that there are no or few differences between the two treatments. 6,7,12,13) However, these studies were conducted in clinical trial settings, and until now there have been no studies carried out in Japan using a nationwide database compiled from real world settings.…”
mentioning
confidence: 99%
“…After a manual review, 118 duplicates and 650 studies irrelevant to our objectives were excluded, and 134 studies remained for further screening. Applying the inclusion and exclusion criteria, a total of 19 studies (four randomized control trials [RCTs], [14][15][16][17] ten meta-analysis studies, [18][19][20][21][22][23][24][25][26][27] three nonrandomized intervention studies, [28][29][30] one cross-sectional study, 31 and one cohort study 32 ) were included for the updated studies for this review (Table 1). Additionally, eight RCTs were also included in this review that were published during the study period of Chou et al 13 and met the inclusion/exclusion criteria, but were not reviewed by them.…”
Section: Methodsmentioning
confidence: 99%
“…18 This study suggested that PEG-IFN alfa-2a plus RBV was more effective than PEG-IFN alfa-2b plus RBV, especially in genotype 1 or 4 HCV patients. Another meta-analysis study by Minami et al 19 found that PEG-IFN alfa-2a was associated with a higher risk of severe adverse events than PEG-IFN alfa-2b (7.45% vs 6.74%, P-value not reported). 19 Additionally, patients with higher doses of PEG-IFN treatment had a higher risk of severe adverse events than those with lower doses (11.94% vs 6.99% for PEG-IFN alfa-2a; 7.10% vs 5.05% for PEG-IFN alfa-2b, P-value not reported).…”
Section: Studies Other Than Rcts Dual Therapymentioning
confidence: 97%
See 1 more Smart Citation